Double‐bundle posterior cruciate ligament reconstruction procedure leads to better restoration of posterior knee laxity in isolated and multiple ligament knee injuries than single‐bundle procedure - Eiji Kondo; Yoshio Nishida; Zenta Joutoku; Daisuke Kawamura; Koji Iwasaki; Masatake Matsuoka; Tomohiro Onodera; Daisuke Momma; Tomonori Yagi; Norimasa Iwasaki; Kazunori Yasuda (Journal of Experimental Orthopaedics, 2025)
ABSTRACT Purpose The purpose of the study was to determine whether the knee stability is better with single‐bundle (SB) or double‐bundle (DB) posterior cruciate ligament (PCL) reconstruction. The hypothesis was that DB PCL reconstruction in isolated and multiple ligament knee injuries may be significantly better in the posterior laxity than SB procedure. Methods A retrospective study was conducted with 51 patients who underwent PCL reconstruction. Seventeen cases required isolated PCL reconstruction, and the others had the following additional ligament reconstruction; 25 cases required anterior cruciate ligament reconstruction, 11 cases required posteromedial corner reconstruction, and eight cases required posterolateral corner reconstruction. All patients were divided into two groups: In Group S, 20 patients underwent SB PCL reconstruction. In Group D, 31 patients underwent DB PCL reconstruction. Clinical outcomes were evaluated at 2 years or more after surgery. The paired Student t‐test, Mann–Whitney U‐test and chi‐square test were used to test for significance. Results The postoperative anterior‐posterior (AP) translation at 20° and 70° and the relative femur‐tibia position in the anterior and posterior stress radiographs at 90° significantly improved postoperatively in both groups. The postoperative side‐to‐side differences in AP translation at 20° and 70° showed no significant difference between the groups. The relative femur‐tibia position in the posterior stress radiographs at 90° was significantly less (p < 0.0001) in Group D (mean, SD, 95% confidence interval; 54.0%, 5.2%, 52.1%–55.8%) than in Group S (43.8%, 5.7%, 41.3%–46.3%). There were no significant differences in the valgus and varus laxities, Lysholm score, International Knee Documentation Committee (IKDC) evaluation, Knee Injury and Osteoarthritis Outcome Score (KOOS), Tegner scale, and complications between the two procedures. Conclusions There were no significant differences in the Lysholm score, IKDC evaluation, and KOOS, Tegner scale between both groups although there was significantly better posterior stability in 90° flexion with DB reconstruction. Level of Evidence Level III.